Comparative Evaluation of Thermotolerant Escherichia coli, Enterococci and Total Coliform as Indicators of Water Quality - Nayma, Jannatun; Chowdhury, Fatema Moni; Ahsan, Sunjukta; Akhter, Marufa Zerin (Bangladesh Journal of Microbiology, 2018)
The present study was aimed to evaluate thermotolerant Escherichia coli and enterococci as alternative water quality indicator bacteria to assess the microbiological quality of surface water and supplied tap water of Dhaka city. Membrane filtration count of total coliform, E. coli and enterococci were obtained from various surface water bodies and supplied tap water. To find out the correlation of these indicators with the presence of water borne pathogens, counts of Salmonella and Vibrio were assessed concomitantly. The identifications of E. coli, Salmonella and Vibrio were performed by biochemical tests; whereas, for enterococci, identification by PCR method was applied. According to USEPA set rule for single sample analysis, the maximum concentration of d”235 E. coli or d”62 enterococci per 100 ml is considered a safe recreational or surface water standard for fresh water bodies. Following this, the present study found that out of the 22 surface water samples studied from 12 different surface water bodies in and around Dhaka city, 13 crossed the limit for E. coli and 10 crossed the limit for enterococci. On the other hand, all of the surface water bodies showed an exceedingly high number of total coliform bacteria regardless of the presence or absence of pathogens. Apart from only one sample, no correlation was observed between the presence of total coliform and the presence of the two pathogenic bacteria studied. On the other hand, E. coli and enterococci showed a better correlation in number with the presence of the pathogens; E. coli showing a better correlation than enterococci. Supplied tap water samples were examined from 8 different locations of Dhaka city. The international set rule is 0 enterococci or E. coli or total coliform or fecal coliform per 100 ml of potable water. All tap water samples showed considerable numbers of both total coliform and E. coli that always exceeded the limit allowed. However, out of the 8 samples, only 3 carried enterococci. Salmonella and Vibrio were obtained from most of the samples. In tap water the occurrence of E. coli showed more correlation with the presence of pathogens than with enterococci. This study suggested that for microbiological quality assessment of surface and tap waters of Dhaka city, total coliform has lost its credibility. Hence, E. coli, enterococci or other alternate water quality indicators suitable for subtropical region should be included in water quality testing. Bangladesh J Microbiol, Volume 34 Number 1 June 2017, pp 7-14